A psychological study of blue collar female workers - Samarasinghe, Gameela; Ismail, Chandrika; Women's Education and Research Centre (Colombo, Sri Lanka) (Colombo : Women's Education & Research Centre, 2000)
With reference to Sri Lanka.
Keywords: Women -- Employment -- Sri Lanka; Blue collar workers -- Sri Lanka -- Psychology